Risk factor analysis for early rebleeding after endoscopic treatment for colonic diverticular bleeding with stigmata of recent hemorrhage. Issue 5 (27th March 2021) - Yamauchi, Atsushi; Kou, Tadayuki; Kishimoto, Takuya; Mori, Yuki; Osawa, Kazuki; Iimori, Kei; Iwano, Kosuke; Kawai, Yuya; Sawada, Kenji; Hamada, Kensuke; Nishimura, Satoshi; Mori, Yoshiharu; et al.
Abstract: Background and Aim: Colonic diverticular bleeding is a common cause of acute lower gastrointestinal bleeding. Endoscopic hemostasis is generally selected as the first‐line treatment; however, a considerable number of patients experience early rebleeding after endoscopic treatment. We investigated the risk factors for early rebleeding after endoscopic treatment. Methods: We retrospectively evaluated the data of 142 consecutive patients who underwent endoscopic treatment (endoscopic clipping or endoscopic band ligation) for colonic diverticular bleeding with stigmata of recent hemorrhage between April 2012 and April 2020. Multivariate logistic regression analysis was conducted to evaluate the statistical relationship between patient characteristics and the incidence of early rebleeding occurring within 30 days after endoscopic treatment. Results: Of 142 patients, early rebleeding was detected in 34 (23.9%) patients. According to univariate analysis, platelet count of <10 × 10 4 /μL, bleeding from the left‐sided colon, and endoscopic clipping usage were associated with early rebleeding ( P < 0.05). The subsequent multivariate logistic regression analysis identified bleeding from the left‐sided colon (odds ratio [OR], 4.16; 95% confidence interval [CI], 1.73–10.0; P = 0.001) and endoscopic clipping usage (OR, 2.92; 95% CI, 1.21–7.00; P = 0.017) as the independent risk factors for early rebleeding. Conclusions: Bleeding from the left‐sided colon and endoscopic clipping usage were the risk factors for early rebleeding after endoscopic treatment. Using endoscopic band ligation was associated with a decreased risk for early rebleeding compared with the use of endoscopic clipping, indicating that endoscopic band ligation was a preferable endoscopic modality to prevent early recurrent bleeding. Abstract : Using endoscopic band ligation was associated with a decreased risk for early rebleeding compared with the use of endoscopic clipping, indicating that endoscopic band ligation was a preferable endoscopic modality to prevent early recurrent bleeding.